There is more to education than the demands of the Industrial Revolution 4.0: A focus on literacy expectations - Fehring, Heather (Advances in Social Sciences Research Journal, 2020)
2020 will bring changing times in education in Australia especially in relation to literacy curriculum policy and procedures. On-going teacher reviews both pre-service and graduate teachers; curriculum reviews especially in relation to the false binary of Synthetic and Analytical phonics and the reconsideration of NAPLAN and PISA following the release of the results of 2018 will be influential in educational policy makers considerations in 2020. In the current education climate, there is an obsession with the so-called Industrial Revolution 4.0. The driving force for change is dominated by market force perspectives of the future needs for industry workforce skills. The Industrial Revolution 4.0 documented in the current literature commenced in the 18th century with the first Industrial Revolution identified as the invention of the steam engine. In relation to educational change, it is important to reflect on two significant issues. First, there is more to education that the provision of workers skilled to meet industry needs. Only examining industrial workforce needs does not cover the total workplace of society. Secondly, education constantly evolves and adapts to factors affecting student learning. This paper explores some of the key issues related to the place of education within the context labelled as the Industrial Revolution 4.0 in 2020.